(3cJGH GdYRdI hGdEfaQGOs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM GdeYeQ GdeSfO CHh GdMSf Hf CHj YHO Gddg GdHZOGOi Ef Cbd GdYjH Ydi GdeQA Cf jLdS ai OGQg hbGd hcjY ai HjJg s
(3BNQgG (B:s
(3aGQLY Edi YLH GdbQBf GdPi dGMjQg ajg cgPG GdTYQ hba YfO YLGjHg BNQ GdLRA GdKGfi ef cJGH GdYRdI hgh BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HBNQg SeGYGJ cKjQgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
Keywords: (3GdJUha hGdBOGH GdTQYjIs